Directing Differentiation of Human Embryonic Stem Cells Toward Anterior Neural Ectoderm Using Small Molecules123. (20th August 2012) - Surmacz, Beata; Fox, Heather; Gutteridge, Alex; Lubitz, Sandra; Whiting, Paul
Abstract: Based on knowledge of early embryo development, where anterior neural ectoderm (ANE) development is regulated by native inhibitors of bone morphogenic protein (BMP) and Nodal/Activin signaling, most published protocols of human embryonic stem cell differentiation to ANE have demonstrated a crucial role for Smad signaling in neural induction. The drawbacks of such protocols include the use of an embryoid body culture step and use of polypeptide secreted factors that are both expensive and, when considering clinical applications, have significant challenges in terms of good manufacturing practices compliancy. The use of small molecules to direct differentiation of pluripotent stem cells toward a specified lineage represents a powerful approach to generate specific cell types for further understanding of biological function, for understanding disease processes, for use in drug discovery, and finally for use in regenerative medicine. We therefore aimed to find controlled and reproducible animal‐component‐free differentiation conditions that would use only small molecules. Here, we demonstrate that pluripotent stem cells can be reproducibly and efficiently differentiated to PAX6 + (a marker of neuroectoderm) and OCT4 − (a marker of pluripotent stem cells) cells with the use of potent small inhibitors of the BMP and Activin/Nodal pathways, and in animal‐component‐free conditions, replacing the frequently used Noggin and SB431542. We also show by transcript analysis, both at the population level and for the first time at the single‐cell level, that differentiated cells express genes characteristic for the development of ANE, in particular for the development of the future forebrain. Stem Cells 2012;30:1875–1884